What determines the performance of strategic alliance managers? Two lens model studies - Zoogah, D.; Peng, Mike (Springer New York LLC, 2011)
Given the increasingly frequent call-often from macro, strategy researchers-for more micro-level probes into the drivers of strategic alliance performance, this article has responded to such a call by leveraging the organizational behavior (OB) and human resource (HR) literature on competencies. Based on two studies drawing on the lens model (Brunswik, 1954), we take on an important but little explored question: "What determines the performance of strategic alliance managers?" In Study 1 (a laboratory study), double system policy capturing results show a positive relationship between alliance competencies and performance judgments. In Study 2 (a field study), we investigate the evaluative behavior of alliance supervisors. Hierarchical linear modeling (HLM) results suggest that some structural, functional, and social competencies are evaluated as more important than other competencies in determining alliance managers' performance.